Pengaruh Gaya Kepemimpinan Transformasional dan Lingkungan Kerja terhadap Produktivitas Kerja Mahasiswa Magang Program Studi Manajemen FBE UII : Kepuasan Kerja sebagai Mediator - Susetya, Puspa Riningtyas; Setyaning, Alldila Nadhira Ayu (Universitas Hamzanwadi, 2024)
Internship serves as a means to enhance students' professional knowledge and skills, producing competent graduates in the workforce, and is expected to have competitiveness upon entering the job market. This study aims to observe the consequences of transformational leadership patterns and the work environment on work productivity through job satisfaction among internship participants in the Management Program at the Faculty of Business and Economics, Universitas Islam Indonesia. This study utilizes questionnaires and SPSS testing tools. The results of the study indicate that transformational leadership patterns cause substantial negative effects, but the work environment leads to positive effects on work productivity. Transformational leadership patterns and the work environment have a significant positive influence on job satisfaction. Job satisfaction has a positive and significant influence on work productivity. Job satisfaction mediates the relationship between transformational leadership patterns, but does not mediate the relationship between the work environment and work productivity